Transformation of pore structure in consolidated silty clay: New insights from quantitative pore profile analysis. (20th October 2018) - Hu, Yong; Li, Yun An; Ruan, Cheng Ke; Lin, Jun Lin; Chen, Shu Jian; Tang, Hui Ming; Duan, Wen Hui
Highlights: Sharp BSE images of pores in silty clay with high resolution and low imaging noise. 2D pore profiles extracted from the sharp BSE images to characterize pores. Transformation of the 2D pore profiles linked with the consolidation process. The Washburn's equation was corrected based on circularity of pores. Abstract: Pore structure provides essential information for studying the behaviors and properties of silty clay in construction projects. This study uses a developed metal intrusion characterization scheme to investigate the transformation of the pore structure of silty clay in consolidation. Clear pore profile images with nanometer-level resolution are produced by BSE imaging. Comparison between metal intrusion and epoxy impregnation suggests minimal alteration of the pore structure of silty clay with the metal intrusion technique. The pore size redistribution and the transformation of porosity indicate that the pores collapse and form during consolidation process. Solidity is found to decrease as consolidation pressure increases, reflecting the consolidation-induced pore deformation. Aspect ratio is found to be independent of the consolidation pressure, indicating that the pores are likely to shrink evenly in consolidation. Two descriptors, box dimension and probability entropy, are found to decrease as consolidation pressure increases, indicating that the overall pore structure becomes homogenized in consolidation. Washburn's equation is modified based on the area–perimeter relation of pores to provide a more accurate reflection of the pore size measurement by mercury intrusion porosimetry. The results show clear evidence for a distinctive two stages transformation processes during consolidation namely radial compaction and pore segregation.